Nosema ceranae in Apis mellifera: a 12 years postdetection perspective. (17th April 2018) - Martín‐Hernández, Raquel; Bartolomé, Carolina; Chejanovsky, Nor; Le Conte, Yves; Dalmon, Anne; Dussaubat, Claudia; García‐Palencia, Pilar; Meana, Aranzazu; Pinto, M. Alice; Soroker, Victoria; Higes, Mariano
Summary: Nosema ceranae is a hot topic in honey bee health as reflected by numerous papers published every year. This review presents an update of the knowledge generated in the last 12 years in the field of N. ceranae research, addressing the routes of transmission, population structure and genetic diversity. This includes description of how the infection modifies the honey bee's metabolism, the immune response and other vital functions. The effects on individual honey bees will have a direct impact on the colony by leading to losses in the adult's population. The absence of clear clinical signs could keep the infection unnoticed by the beekeeper for long periods. The influence of the environmental conditions, beekeeping practices, bee genetics and the interaction with pesticides and other pathogens will have a direct influence on the prognosis of the disease. This review is approached from the point of view of the Mediterranean countries where the professional beekeeping has a high representation and where this pathogen is reported as an important threat.